Assessment of Quality of Life in Young Patients with Single Ventricle after the Fontan Operation - Uzark, Karen; Zak, Victor; Shrader, Peter; McCrindle, Brian W.; Radojewski, Elizabeth; Varni, James W.; Daniels, Kaitlyn; Handisides, Jill; Hill, Kevin D.; Lambert, Linda M.; Margossian, Renee; Pemberton, Victoria L.; et al. (The Journal of pediatrics, 2016)
To assess self-reported quality of life (QOL) in a large multicenter cohort of adolescent and young adults surviving Fontan. Cross-sectional. The Pediatric Quality of Life Inventory (PedsQL) was administered to 408 survivors of Fontan ages 13-25 years enrolled in the Pediatric Heart Network Fontan Follow-up Study. Subjects also completed either the Child Health Questionnaire (age <19 years) or Short Form Health Survey (age ≥19 years). PedsQL data were compared with matched controls without a chronic health condition. Correlations between the measures were examined. Mean PedsQL scores for subjects receiving Fontan were significantly lower than those for the control group for physical and psychosocial QOL (P < .001). Overall, 45% of subjects receiving Fontan had scores in the clinically significant impaired range for physical QOL with 30% in the impaired range for psychosocial QOL. For each 1 year increase in age, the physical functioning score decreased by an average of 0.76 points (P = .004) and the emotional functioning score decreased by an average of 0.64 points (P = .03). Among subjects ≥19 years of age, the physical functioning score decreased by an average of 2 points for each year increase in age (P = .02). PedsQL scale scores were significantly correlated with conceptually related Child Health Questionnaire (P < .001) and Short Form Health Survey scores (P < .001). Survivors of Fontan are at risk for significantly impaired QOL which may decline with advancing age. Routine assessment of QOL is essential to inform interventions to improve health outcomes. The PedsQL allowed QOL assessment from pediatrics to young adulthood. ClinicalTrials.gov: NCT00132782.